Bioinformatic analysis of differentially expressed genes in porcine intestinal epithelial cells infected with transmissible gastroenteritis virus - Xu-xuan ZHANG; Guo-wei LAN; Zhe WANG; Chen-hao JIANG; Jing XI; Yao LI; Jun QIAO; Yan REN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
Transmissible Gastroenteritis Virus (TGEV) infection is one of the leading causes of diarrhea in piglets. Intestinal immune system plays an important role in maintaining the intestinal mucosa"s integrity and resisting infection by pathogens. However, the relationship between the immune response induced by TGEV infection and disease progression is unclear. Using the microarray data set GSE41756 from the Gene Expression Omnibus database, we analyzed porcine small intestinal epithelial cells at 6 and 12 h of TGEV infection. Differentially expressed genes (DEGs) were detected using the "limma" R package. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes pathway enrichment, and the protein-protein interaction network analyses were performed with the detected DEGs. We found 56 DEGs (47 up-regulated and 9 down-regulated) after the intersection. Pathway enrichment analysis revealed that the DEGs were mainly associated with immune response, extracellular space, cytokine activity, and positive regulation of nuclear factor-κB import into the nucleus. This revealed the strong relationships among DEGs in the tumor necrosis factor signaling pathway, inflammatory bowel disease, and influenza A. Interleukin 6 (IL6), IL8, IL18, tumor necrosis factor, and toll-like receptor hub genes may play important roles during TGEV infection.